Analisis Pengaruh Kecerdasan Emosional, Spiritual, Sosial dan Fasilitas Pembelajaran Terhadap Tingkat Pemahaman Akuntansi - Djoko Kristianto; Suharno Suharno (RESEARCH FAIR UNISRI, 2020)
This study aims to analyze the influence of intellectual, emotional, spiritual, social and learning facilities on the level of accounting understanding. While respondents in this study were accounting students of the seventh semester of the Faculty of Economics at Slamet Riyadi University, total 84 students. The results of the study 1)) obtained the value of Sig (0.043) <0.05 means that emotional intelligence influences the understanding of accounting, 2) The calculation results obtained Sig (0.565)> 0.05 which means there is no influence of spiritual intelligence on the level of accounting understanding , 3) The calculation results obtained Sig (0.224)> 0.05 means there is no influence of social intelligence on the level of understanding of accounting and, 4) The calculation results obtained Sig (0.048) <0.05 this means there is an influence of learning facilities on level of understanding of accounting.Keywords: Emotional Intelligence, Spiritual, Social and Accounting Understanding Level